Optimalisasi Penempatan Tower Crane Pada Proyek Pembangunan Gedung Pascasarjana, Universitas Riau - Salsabila, Assyfa; Iriana, Rian Trikomara; Djuniati, Sri; Sebayang, Mardani; Elianora, Elianora (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
The increase in building and infrastructure development in Indonesia demands effectiveness and efficiency in construction projects, particularly in the selection and placement of heavy equipment such as tower cranes. This study focuses on optimizing the placement of a tower crane in the construction project of the Graduate Building of Universitas Riau, planned to have 6 floors with a height of 31.45 meters. The main issues include delays in structural progress and the tower crane being positioned close to the maximum jib reach, which decreases lifting speed and increases cycle time, ultimately raising operational costs. The research aims to find a placement that maximizes productivity and minimizes operational costs. The methods employed include direct observation and interviews. Observations were conducted on 20 columns at elevation 13.45 meters on the 3rd floor to determine the tower crane cycle time. Data analysis compared cycle times between the existing placement and two alternative placements. The study results indicate that the existing placement requires 598.195 hours with operational costs of Rp1,402,373,077.80, while alternative 7 requires 590.637 hours costing Rp1,389,917,824.27, and alternative 9 requires 606.393 hours costing Rp1,415,882,093.32. The time and cost difference between alternative 7 and the existing setup is 7.558 hours faster and Rp12,455,253.54 cheaper. Hence, the optimal position for the tower crane is alternative 7 at coordinates 764722.537; 53537.493. This placement demonstrates that a shorter distance between the tower crane and the supply point enhances productivity and reduces operational costs.